Enhancing Student Retention Through School Coherence: The Mediating Role of School Climate - Dallasheh, Waleed (Journal of Ecohumanism, 2025)
This study explores the impact of school coherence on student dropout rates in Arab schools in Israel, with school climate as a mediating factor. School coherence - characterized by strong leadership, structured collaboration, and aligned instructional practices - is examined for its role in fostering student retention. Additionally, the study assesses how teachers’ demographic characteristics influence dropout trends. A quantitative research design was employed, gathering data from 345 teachers across 17 secondary schools (12 regular, 3 private, and 2 technological) in northern Israel. The results indicate a strong positive correlation between school coherence and school climate (r = 0.36, p < 0.001), suggesting that greater coherence contributes to a more supportive and structured learning environment. Furthermore, significant negative correlations were found between school coherence and student dropout rates (r = -0.21, p < 0.001), as well as between school climate and dropout rates (r = -0.32, p < 0.001), reinforcing the role of a positive school climate in reducing dropout risks. The study also identifies a relationship between teachers’ demographic factors (age, tenure, and specialization) and student dropout rates. The findings highlight the necessity of strengthening school coherence to improve school climate, ultimately reducing student attrition. These insights offer valuable implications for educational policymakers and practitioners aiming to develop strategic interventions for dropout prevention in Arab schools in Israel.